Theoretical Issues on Contemporary Methods of Estimate the Lifetime Value of Hypermarket Business: Geospatial Approach as New Method - Bohari, Abdul Manaf; Rainis, Ruslan; Marimuthu, Malliga (Journal of Asian Business Strategy, 2012)
The business profitability is an important issue for the hypermarket business around the world and vast literature was found on its measurements, model, and approaches of studied. In general, related literature showed that various methodologies have been used to estimate the profitability via specific model where dominating by financial and accounting based instrument with specific aims on maximizing the customer lifetime value (CLV). In fact, the measurements that have been used are arising some issues on theoretical part of the CLV estimation which it has faced some problem regarding customer evaluation as a centre part of CLV. Traditionally, financial or accounting variables has been improved and reused in different ways continuously, where the method it self in is still stagnant as before. The objective of this paper is to overview the theoretical issues of contemporary method based on the CLV related model of financial and accounting of estimating hypermarket profitability. Secondly, this paper is highlighting the geospatial method as new way for estimate the CLV of hypermarket. In future, the potential use of geospatial method will be brings new hope on better predication the CLV which considers non-financial variables as compared to traditional CLV method.